Green technology an A-to-Z guide - Mulvaney, Dustin (SAGE reference series on green society., 2011)
Featuring such disciplines as nanoscience, biochemistry, information technology and environmental engineering, in 150 articles this volume explores the essential role of technology in developments towards a sustainable environment.